Respuesta :
[tex]\bold{\huge{\purple{\underline{ Solution }}}}[/tex]
{Correct Question :-
Show that,
[tex]\bold{\dfrac{ 2}{2x+11}}{\bold{-}}{\bold{\dfrac{ 1}{x - 4}}}{\bold{=}}{\bold{\dfrac{1}{2}}}[/tex]
Simplifies to,
[tex]\bold{ 2x² + 3x - 6 = 0 }[/tex]}
Here, We have to show that,
[tex]\bold{\blue{\dfrac{ 2}{2x+11}}}{\bold{\blue{-}}}{\bold{\blue{\dfrac{ 1}{x - 4}}}}{\bold{\blue{ = }}}{\bold{\blue{\dfrac{1}{2}}}}{\bold{\blue{= 2x² + 3x - 6 = 0}}}[/tex]
Let's Begin :-
[tex]\bold{\dfrac{ 2}{2x+11}}{\bold{-}}{\bold{\dfrac{ 1}{x - 4}}}{\bold{=}}{\bold{\dfrac{1}{2}}}[/tex]
- By taking LCM of the given Denominators
[tex]\sf{\dfrac{ 2(x-4) - 1(2x + 11)}{(2x+11)(x-4)}}{\sf{=}}{\sf{\dfrac{1}{2}}}[/tex]
- By solving the like terms
[tex]\sf{\dfrac{ 2x - 8 - 2x - 11)}{2x(x-4)+11(x - 4)}}{\sf{=}}{\sf{\dfrac{1}{2}}}[/tex]
[tex]\sf{\dfrac{ - 19 }{2x² -8x + 11x - 44}}{\sf{=}}{\sf{\dfrac{1 }{2}}}[/tex]
[tex]\sf{\dfrac{ - 19 }{2x² + 3x - 44}}{\sf{= }}{\sf{\dfrac{1}{2}}}[/tex]
- By cross multiplying the numerator and denominator
[tex]\sf{ - 19 × 2 = 2x² + 3x - 44}[/tex]
[tex]\sf{ - 38 = 2x² + 3x - 44 }[/tex]
[tex]\sf{ 0 = 2x² + 3x - 44 + 38}[/tex]
- After, Solving the given equation we proved that 2x² + 3x - 6 = 0
[tex]\bold{ 2x² + 3x - 6 = 0 }[/tex]
Hence, It is proved
[tex]\bold{\dfrac{ 2}{2x+11}}{\bold{-}}{\bold{\dfrac{ 1}{x - 4}}}{\bold{ = }}{\bold{\dfrac{1}{2}}}{\bold{= 2x² + 3x - 6 = 0 }}[/tex].
The required equation has been proved as shown
Expressions and equations
We are to show that 2/(2x+11) - 1/(x-4) = 1/2
Find the LCM of the expression
[tex]\frac{2(x-4)-(2x+11)}{(2x+11)(x-4)}=\frac{1}{2}\\ \frac{2x-8-2x-11}{(2x+11)(x-4)}=\frac{1}{2}\\[/tex]
Cross multiply
(2x+11)(x-4) = -19(2)
2x^2 -8x + 11x - 44 = -38
2x^2 + 3x = -38 + 44
2x^2 + 3x = 6
2x^2 + 3x - 6 = 0 (prove)
The required equation has been proved
Learn more on proofs here: https://brainly.com/question/1788884